PENGARUH EDUKASI MEKANISME KOPING DENGAN MEDIA AUDIOVISUAL TERHADAP TINGKAT KECEMASAN PASIEN PRE OPERASI DI RS PKU MUHAMMADIYAH GAMPING - Prasetya, Oktafian Aldi; Purnamasari, Vita; Riyadi, Raden Sugeng (Jurnal Ilmiah Kesehatan, 2025)
Purpose: The study aims to determine the effect of coping mechanism education using audiovisual media on the anxiety levels of pre-operative patients at PKU Muhammadiyah Gamping Hospital. Methods: This study employed a quantitative approach with an experimental research method. The research design used was a pre-experimental design with a one-group pretest-posttest. Samples were taken using random sampling techniques and calculated using the Slovin formula. Results: The probability value in the non-parametric Wilcoxon statistical test was 0.000, indicating a significant difference in the anxiety levels of pre-operative patients at PKU Muhammadiyah Gamping Hospital before and after receiving coping mechanism education using audiovisual media. Conclusion: There is an effect of providing coping mechanism education using audiovisual media on the anxiety levels of pre-operative patients, with a p-value of 0.000.